Teacher as a factor of improvement of teaching physical education effects for younger school pupils - Gorica Bilak - Moconja; Radenko Dobraš; Goran Tadić; Aleksandar Kukrić; Borko Petrović; Darko Stojanović (University of Banja Luka, Faculty of physical education and sport, 2018)
The aim of this research is to show the effects of experimental treatment in physical education in children aged 10-11 years. Experimental treatment lasted in the period 01.03.2010. until 01.03.2011. In 16 primary schools in the Republic of Srpska / BiH, which included the volunteering of 20 graduated professors of physical education without work experience in the fourth and fifth grades of elementary schools, who conducted physical education classes instead of teachers of class teaching, that is teachers, who, in accordance with the legal provisions spend lessons in the specified age. The treatment involved 1558 pupils and students from urban and suburban areas, of which 1,213 were in experimental and 345 in the control group. All students were tested with a battery of "Eurofit" tests, ie seven variables in the field of motor skills were analyzed. The treatment was approved by the Ministry of Family, Youth and Sports and the Ministry of Education and Culture of the Government of the Republic of Srpska, and it was implemented in accordance with the Curriculum and Program in cooperation with these two ministries, the Faculty of Physical Education and Sport of the University of Banja Luka and the Republic Pedagogical Institution. After the initial and final measurement of the experimental and control group of students, it was concluded that the students of the experimental group achieved statistically significantly better results in the tests of motor abilities. Since the experimental treatment lasted for a year, and that all subjects were tested using the same methods under the same conditions, and by inspecting the comparison results of the final measurements, it can be said that the work of graduated physical education teachers in the teaching of physical education of the younger school age positively influenced the development tested motor skills of students.